PRODUCTION, STRUCTURE AND PROPERTIES OF CHROMIUM BRONZE ALLOYED MECHANICALLY WITH THE MELTING OF NANOCRYSTALLINE MODIFYING LIGATURES - F. G. Lovshenko; G. F. Lovshenko; I. A. Lozikov (Литьë и металлургия)
The reactive mechanical alloying is an effective technology for production of nanocrystalline modifying modifiers and ligatures. During smelting chromium bronzes use of mechanically alloyed modifying ligatures allow to exclude from the technology the environmentally hazardous high-temperature process of production of cast ligatures and to reduces reduce the optimum temperature of the melt alloying process copper at 50–100 °C by reducing its duration 2, 5–3,5 times This excluded process requires expensive furnace equipment. Mechanically alloyed modifying ligatures allow the formation of dispersion-strengthened heat-resistant materials with sub -,/ microcrystalline structure type bases, which are strength, hardness, conductivity and temperature of the onset of recrystallization about 15–20% superior to the base, which increases the resistance of the welding electrodes by 1.8–2.2 times.